Penerapan Media Pembelajaran Audio Visual untuk Meningkatkan Minat Belajar Siswa Kelas V di SDN Sukaharja 3 - Amanda Syabila Putri Maulana; Maya Maya; Muhammad Hafidz Wahyudin; M. Makbul; Neneng Suryani (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
Low student interest in Islamic Religious Education subjects is one of the obstacles found in fifth-grade students at SDN Sukaharaja 3. This situation manifests as students' lack of attention during learning, rapid fatigue, and limited participation in educational activities. Strategies have been adopted to address this problem through the use of audiovisual materials that make the learning process more interesting and participatory. This study aims to investigate the use of audiovisual resources to increase the interest of fifth-grade students at SDN Sukaharaja 3. This study uses a Classroom Action Research (CAR) approach, which takes place in two cycles, each including the planning, implementation, observation, and reflection phases. Data collection is carried out through observation, testing, documentation, and assessment to measure student interest. The results of the study indicate that the use of audiovisual resources can increase student interest. In the first cycle, the average student engagement score reached 65% in the